2022
DOI: 10.5603/cj.a2022.0072
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel inhibition with amiodarone or verapamil in symptomatic hospitalized nonintensive-care COVID-19 patients: The ReCOVery-SIRIO randomized trial

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Cardiology Journal" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Previous studies investigating CCB associations with similar outcomes have found mild benefits [20,21,33,34]; however, these were all associated with limitations such as a small sample size (i.e., less than 25) or a lack of adjustment for race as a confounder. A recently concluded multicenter, international clinical trial, the Recovery-SIRIO (NCT04351763) study, found that neither amiodarone nor verapamil significantly accelerated short-term clinical improvement [35], which is in agreement with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies investigating CCB associations with similar outcomes have found mild benefits [20,21,33,34]; however, these were all associated with limitations such as a small sample size (i.e., less than 25) or a lack of adjustment for race as a confounder. A recently concluded multicenter, international clinical trial, the Recovery-SIRIO (NCT04351763) study, found that neither amiodarone nor verapamil significantly accelerated short-term clinical improvement [35], which is in agreement with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the trial with Umifenovir revealed that it was ineffective in shortening the duration of SARS-CoV-2 in severe patients and did not improve the prognosis in non-ICU patients and mortality ( Darazam, 2021 ). Neither Amiodarone nor Verapamil too, were found to significantly accelerate short-term clinical improvement in hospitalised COVID-19 patients ( Navarese et al, 2022 ). Although overall results reported for Nafamostat were not highly encouraging, one group observed a shorter median time to clinical improvement in a small group of high-risk COVID-19 patients requiring oxygen treatment ( Zhuravel, 2021 ; NCT04623021).…”
Section: Sars-cov-2 Entry Inhibitors In Clinical and Preclinical Testingmentioning
confidence: 97%
“…Tummino et al [3] established that the threshold concentration for inducing phospholipidosis in cultured cells is correlated to the antiviral activity. Several drugs from the list, including chloroquine, hydroxycholoquine and amiodarone, have been investigated in clinical trials for COVID-19 treatment or prevention, but without success [2,3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%